Handsight: Hand-Mounted Device untuk Membantu Tunanetra Berbasis Ultrasonic dan Arduino - Eko Setyo Purnomo; Adian Fatchur Rochim; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2015)
Generally, blind people use a cane to know the distance around them. A cane was normally use when they walk outdoors, but if the cane used in indoors; it is not used because of fear of damaging the goods-glassware. Another disadvantage of the stick was usually used just to feel the objects / obstacles below the blinds, and other obstacles such as cars or trucks, which often not detected by the cane. Blind people also have constraints to determine the distance of nearby objects, such as people to talk to, etc. The main component of the system is sensor HC-SR04 used to scan the surrounding area by emitting ultrasonic waves. Echoes from objects were use as an input to microcontroller, and then it used to determine the direction and the distance of objects around the blinds using the servo arm movement and buzzer sound. The design of the device utilizes the theory of sound waves velocity in the air, and it was carried out in several steps. The first step is making the hardware device, which uses sensor HC-SR04, micro servo Tower Pro, and power supply of nine Volt battery. The test result shows that the system is able to detect objects with a range of 60 degrees. The design of the device was valuable because it is wearable which can be attached to the back of the hands. Conceptually, the device has met the basic criteria that detect objects and give feedback to the user. Some things that can be improved are power supply and increasing device responsibility so it is able to read distance and give feedback more accurately and more quickly.